2014
DOI: 10.1007/s12223-014-0333-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of five newly isolated bacteriophages active against Pseudomonas aeruginosa clinical strains

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that causes serious infections, especially in patients with immunodeficiency. It exhibits multiple mechanisms of resistance, including efflux pumps, antibiotic modifying enzymes and limited membrane permeability. The primary reason for the development of novel therapeutics for P. aeruginosa infections is the declining efficacy of conventional antibiotic therapy. These clinical problems caused a revitalization of interest in bacteriophages, which are highly sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…5 μL of 0.5% uranyl acetate was then applied to the grids, and excess solution was immediately removed, and grids were air-dried. Samples were viewed with the FEI Tecnai G2 S-Twin Transmission Electron at an operating voltage at 80 KV (Sangha et al, 2014; Kwiatek et al, 2015; Stalin and Srinivasan, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 μL of 0.5% uranyl acetate was then applied to the grids, and excess solution was immediately removed, and grids were air-dried. Samples were viewed with the FEI Tecnai G2 S-Twin Transmission Electron at an operating voltage at 80 KV (Sangha et al, 2014; Kwiatek et al, 2015; Stalin and Srinivasan, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The latent period was defined as the time interval between the adsorption and the beginning of the initial rise in the phage count. The burst size of respective phages was calculated as the ratio of the final phage titer to the initial count of infected bacterial cells during the latent period (Agudelo Suárez et al, 2002; Kwiatek et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…[99][100][101] There is even an indication that the phages containing WP1, WP2, WP3, WP4, and WP5 are capable of lysing antibiotic-resistant bacteria, as in the case of MDR and XDR P. aeruginosa. 102 After an in vitro investigation, it was realized that phage ϕkm18p is able to effectively lyse the most XDR A. baumannii and also using of phages as a cocktail has the potential of lysing XDR A. baumannii isolates of all various genotypes. 45 The effect of ϕKMV, ϕPA2, ϕPaer4, and ϕE2005 phages on 11 strains of MDR, and 1 strain of XDR were tested by Abigail and et al The results demonstrated that phages were able to lyse MDR P. aeruginosa and prevent biofilm formation, however, no effect on XDR P. aeruginosa lysis was detected.…”
Section: Global Concern For Mdr Xdr and Pdr Pathogensmentioning
confidence: 99%
“…pathogens that are currently being targeted for phage therapy. For example, although phage treatments in experimental P. aeruginosa, K. pneumoniae, and A. baumannii infections in animal models have exhibited efficacy [62][63][64][65], phages specific for P. aeruginosa, K. pneumoniae, and A. baumannii have limited host ranges, usually 5%-50% [65][66][67]. Thus, a mix of several phages in a cocktail must be used to cover the diversity of clinically important strains.…”
Section: Designing and Building Fixed Phage Cocktails For Off-the-shementioning
confidence: 99%